Design of the BAZNAS Santripreneur Application for Strengthening Digital-Based Student Technopreneurship - Muhammad Romadhona Kusuma (Proceeding of International Conference on Islamic Boarding School, 2025)
The Santripreneur Program is an initiative of Badan Amil Zakat Nasional (BAZNAS), the official National Zakat Agency of Indonesia, aimed at empowering final-year students and alumni of Islamic boarding schools in the field of entrepreneurship. This article aims to design a supporting digital application to strengthen the implementation of the Santripreneur program in response to the evolving landscape of technopreneurship. This study uses a user-centered software engineering approach, by identifying key features to support entrepreneurship training, product marketing, access to business assistance, and mentoring. The design results consist of web-based and mobile systems that provides a training dashboard, halal product catalog, consultation modules, and a business performance evaluation system. This application is expected to support the sustainability of the Santripreneur program and expand the reach of its benefits in Islamic boarding schools nationally. With the support of digital infrastructure, students are encouraged to become independent, productive, and globally competitive technopreneurs, The final design also shows strong potential to enhance program impact through an integrated and scalable digital ecosystem tailored to the needs of santri communities.